2004
DOI: 10.1111/j.1365-2249.2004.02624.x
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-βup-regulates the expression of co-stimulatory molecules CD80, CD86 and CD40 on monocytes: significance for treatment of multiple sclerosis

Abstract: SUMMARYInterferon (IFN)-b reduces the biological activity of multiple sclerosis (MS), a presumably T cellmediated autoimmune disease of central nervous system (CNS) myelin. Co-stimulatory molecules are necessary for full T cell activation and differential expression of co-stimulatory molecules on antigenpresenting cells is thought to influence the type of effector T cell response (Th1/Th2). In this study we investigated the effects of IFN-b on the expression of co-stimulatory molecules on lymphocytes and monoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 54 publications
3
39
0
Order By: Relevance
“…As described previously [19,22,43,44] CD40 and CD80 expressions on CD14 + monocytes were not detected in four of six and in five of six controls, respectively. In contrast, in monocytes from PBMC isolated from 10 patients immediately after surgery, CD40 and CD80 were expressed in seven and four patients, respectively, although this did not amount to statistically significant differences.…”
Section: Expression Of Cd40 Cd80 Tlr2 Tlr4 and Ccr7 On Monocytes Asupporting
confidence: 69%
“…As described previously [19,22,43,44] CD40 and CD80 expressions on CD14 + monocytes were not detected in four of six and in five of six controls, respectively. In contrast, in monocytes from PBMC isolated from 10 patients immediately after surgery, CD40 and CD80 were expressed in seven and four patients, respectively, although this did not amount to statistically significant differences.…”
Section: Expression Of Cd40 Cd80 Tlr2 Tlr4 and Ccr7 On Monocytes Asupporting
confidence: 69%
“…TLR ligand‐induced up‐regulation of co‐stimulatory molecules including B7‐1 depends on type I IFN signalling . Here we show that podocytes can recognize a variety of different TLR ligands and mount a type I IFN response that triggers actin remodelling and B7‐1 induction, thereby leading to proteinuria.…”
Section: Introductionmentioning
confidence: 79%
“…Several studies demonstrated that keratinocytes in the viable epidermis produced various cytokines that were released into the surrounding environment when skin was exposed to physical stimuli associated with barrier disruption. 44,[49][50][51] Therefore, physical stimuli to the skin may induce the release of immune cytokines from living cells such as keratinocytes and sustainably affect the activation of LCs and dDCs in an indirect manner.…”
Section: Discussionmentioning
confidence: 99%